Model Lengkung Bentuk Batang (Taper Curve) Pohon Jati (Tectona Grandis) - Ronggo Sadono; Muhammad Dimas Trisnomo; Askar Askar (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Model of Taper Curve of Teak Stem (Tectona grandis)Detailed information on tree volume for fancy wood, such as teak, is important to estimate its financial value. Therefore, a method of estimating stem volume in portion wise is developed. The objective of this study was to apply a parabolic taper curve in various tree strata. Data of stem diameter at any relative height were collected from selected felled-tree samples according to stem quality both in the state and community forests by section wise measurement. Regression analysis was applied to estimate parameter and to test the suitability level of the parabolic taper model. The results showed that parabolic taper model could be used to describe the stem curve of clear bole stem in state forest and the stem curve up to tree height with minimum diameter of ca. 10 cm. In the state forest, the parabolic taper model was fit to medium and large diameter classes or in the intermediate and dominant strata. For small diameter class or in suppressed stratum, the model was not sufficiently fit. On the other hand, the parabolic taper model was fit to all samples from community forests because the samples comprised the stem of best quality from the stand. The parabolic taper model was suitable to apply on high quality stems which were characterized with healthy, cylindrical, and straight stem, high clear bole, and straight grain.